Metallothionein Defensive Strategies against Metal Overload in Farm Animals - Nachappa MN, Dhyan Chandra Yadav, Chandana Maji (Revista Electronica de Veterinaria, 2024)
The comprehensive research highlights the possible health effects of metal overload, which is the condition of farm animals having an excess of metallic components like lead or copper. The study, which spans the years 2019 through 2023, offers a thorough review of defense mechanisms with a particular emphasis on metallothionein (MT) defensive strategies. Utilizing information from 37 pertinent research studies, the paper discusses important metals such as Ni, Cd, Cu, Fe, Zn, As ,Co, Pb, Hg and Cr, clarifying their effects and limits, particularly concerning topical and intramuscular applications. Particular focus is placed on the harmful effects of mercury pertaining to the reproductive, immune and central neurological systems. To lessen the negative impacts of metal overload on animal health, the article supports regulatory actions as well as environmental pollution mitigation. Together with antioxidants, metal-binding proteins, enzymatic and non-enzymatic defense mechanisms, MT becomes an essential defensive strategy. The importance of vitamins, minerals, proteins and phyto-nutrients in preventing oxidative stress brought by an excess of metals is covered in the last section. MT induction provides farm animals with a useful defense against metal overload while preserving physiological balance because metal-binding proteins like metalloreductase and ceruloplasmin maintain copper-iron balance. Metallothionein, crucial for farm animals' metal homeostasis, is essential for protecting against metal overload. Understanding its regulation is crucial for sustainable animal husbandry practices.